Faktor Risiko yang Mempengaruhi Kejadian Malaria di Wilayah Kerja Puskesmas Moru Kabupaten Alor - Amina A. Alipen; Sigit Purnawan; Amelya B Sir (Yayasan Literasi Sains Indonesia, 2024)
Malaria is an infectious disease that has the potential for an epidemic. Based on data from the Alor District Health Service, positive malaria cases in 2020 212 cases, in 2021 there were 53 cases, and in 2022 there were 411 cases. The research aims to analyze the risk factors that influence the incidence of malaria in the Moru Health Center working area. This research is an analytical observational study with a case-control study research design. The research was conducted in the Moru Community Health Center working area, Alor Regency. The population in this study, namely the case population, is people who tested positive for malaria during laboratory examination and the control population is people who tested negative for malaria during laboratory examination. The samples in this study were 76 case samples and 76 control samples with a ratio of 1:1 obtained using a simple random sampling technique—data collection through interviews and observations. The results of the study showed the influence of knowledge (p=0.004; OR=2.429), use of wire mesh (p=0.001; OR=3.0), the presence of mosquito breeding places (p=0.010; OR=2.216) and the habit of doing activities outside the home at night. (p=0.004; OR=2.412) on the incidence of malaria in the Moru Health Center working area. It is hoped that the public will increase their knowledge by participating in outreach or counseling activities and taking steps to prevent mosquito bites, such as wearing long-sleeved shirts and trousers when leaving the house at night and installing wire mesh on ventilation.